2018
DOI: 10.1007/s12035-018-1260-0
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic Acid (DHA) Induced Morphological Differentiation of Astrocytes Is Associated with Transcriptional Upregulation and Endocytosis of β2-AR

Abstract: Docosahexaenoic acid (DHA), an important ω-3 fatty acid, is abundantly present in the central nervous system and is important in every step of brain development. Much of this knowledge has been based on studies of the role of DHA in the function of the neurons, and reports on its effect on the glial cells are few and far between. We have previously reported that DHA facilitates astrocyte differentiation in primary culture. We have further explored the signaling mechanism associated with this event. It was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 110 publications
0
14
0
Order By: Relevance
“…It is worthy to mention that many (but not all) of these studies show greater efficacy of EPA than DHA, while our studies suggest equal potency and efficacy for the two compounds [14, 52, 5658]. Note, however, that 1) the EPA- or DHA-“enriched” preparations used in clinical studies are 80:20 mixtures of the two n-3 PUFA species and 2) orally-ingested preparations are metabolized, something that does not occur in cell-culture medium…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…It is worthy to mention that many (but not all) of these studies show greater efficacy of EPA than DHA, while our studies suggest equal potency and efficacy for the two compounds [14, 52, 5658]. Note, however, that 1) the EPA- or DHA-“enriched” preparations used in clinical studies are 80:20 mixtures of the two n-3 PUFA species and 2) orally-ingested preparations are metabolized, something that does not occur in cell-culture medium…”
Section: Discussionmentioning
confidence: 74%
“…Some reports have indicated that n-3 PUFA treatment could impact the neuronal differentiation in primary cultured animal NSCs [51]. A recent report indicated that DHA could enhance astrocyte-like morphologic formation in rat astrocytes [52]. Here, taking the advantages of iPSC technology, the effect of n-3 PUFAs on astrocyte differentiation from patient-derived iNSCs was tested.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, in-depth investigation was conducted to uncover the modulatory role of miR-145 in G i -based β2AR signaling. The cAMP response element binding protein (CREB), which binds to cAMP response element in the promoter of β2AR gene, can facilitate the expression of β2AR [ 20 ]. In addition, CREB was also demonstrated to be a downstream target of protein kinase B (Akt), and a previous study indicated that miR-145 could remarkably promote the phosphorylation of Akt [ 21 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…DHA attenuates microglial-induced inflammation by inhibiting the NFκB and MAPK pathway [ 59 ], while DHA deficiency increases the expression of pro-inflammatory cytokines such as IL-6, IL-1β or TNF-α [ 76 ]. DHA is crucial for the differentiation of astrocytes and inhibits ER stress [ 77 , 78 ]. On the other hand, ARA acts as a messenger controlling the electrical and biochemical behavior of neurons and glial cells.…”
Section: Fatty Acid Synthesis In Glial Cellsmentioning
confidence: 99%